Hadith #5160 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ibrahim bin Musa al-Razi al-Fara' إبراهيم بن موسى الرازي الفراء; Ma'mar bin Rashid معمر بن راشد; Uthman bin Zufar bin Muzaham عثمان بن زفر بن مزاحم (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by al-A’mash in a similar way to same way to the same effect through a different chain of narrators.
Grade: Sahih

Hadith #5161 - Sunan Abi Dawud - Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Muhammad bin Khalid bin Rafa'i محمد بن خالد بن رافع; Uthman bin Zufar bin Muzaham عثمان بن زفر بن مزاحم (Sunan Abi Dawud)
The Prophet (ﷺ) said: Feed those of your slaves who please you from what you eat and clothe them with what you clothe yourselves, but sell those who do not please you and do not punish Allah’s creatures.
Grade: Sahih